2019
DOI: 10.1105/tpc.18.00334
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Endoplasmic Reticulum-Localized UBAC2 Proteins Interact with PAMP-INDUCED COILED-COIL to Regulate Pathogen-Induced Callose Deposition and Plant Immunity

Abstract: Pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) is initiated upon PAMP recognition by pattern recognition receptors (PRR). PTI signals are transmitted through activation of mitogen-activated protein kinases (MAPKs), inducing signaling and defense processes such as reactive oxygen species (ROS) production and callose deposition. Here, we examine mutants for two Arabidopsis thaliana genes encoding homologs of UBIQUITIN-ASSOCIATED DOMAIN-CONTAINING PROTEIN 2 (UBAC2), a conserved endoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…The ubiquitin-associated domain-containing protein 2(UBAC2) gene is located on chromosome 13q32.3 and encodes UBAC2 protein that is a highly conserved protein in different species 6 , 7 . It was reported that the polymorphism of UBAC2 gene was related to Behcet’s disease and UBAC2 gene was the risk allele of Behcet’s disease 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitin-associated domain-containing protein 2(UBAC2) gene is located on chromosome 13q32.3 and encodes UBAC2 protein that is a highly conserved protein in different species 6 , 7 . It was reported that the polymorphism of UBAC2 gene was related to Behcet’s disease and UBAC2 gene was the risk allele of Behcet’s disease 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these results were further confirmed by the experiments of cell death and callose deposition, which are one of the multiple defense responses involved in wheat all-stage resistance against stripe rust infection [13]. Previous studies have indicated that callose deposition likely plays a key role in limiting colonization and, subsequently, prevent sporulation in some plants [37,38]. Similarly, we found that wheat plants promote a defense response through callose deposition after Pst infection, especially in the compatible system.…”
Section: Discussionmentioning
confidence: 57%
“…Whether the same situation exists in Foc R1 and Foc TR4 and other plant pathogens remains to be verified. On the other hand, the callose deposited by plants in response to pathogen invasion is also a type of glucan endo-1,3-beta-glucon [ 27 ]. Beta-1,3-glucanase expression by plants reduced callose deposition and facilitated invasion by pathogens [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%